Skin graft on a collagen and elastin matrix fixed with negative pressure in a complicated pediatric dog bite: case report - Fattel-Servin, Omar S.; Guevara-Valmaña, Osvaldo I.; Trigueiros-Guzmán, Sebastian; Prieto-Vargas, Valentina; Ramirez-Morales, Ximena I.; Apellaniz-Campo, Armando (International Surgery Journal, 2024)
Animal bites represent a significant source of morbidity in the pediatric population, with dogs being the primary cause. Highlighting the need for innovative solutions to effectively tackle the issue and enhance both functional and aesthetic outcomes. Dog bites, marked by a heightened morbidity rate, present an inherent infection risk owing to the considerable bacterial load present in saliva. The fundamental approach to treatment revolves around preventing infection through meticulous washing, debridement, and the timely implementation of early primary closure. We detail the management of a pediatric patient with a dog bite on the pelvic limb, resulting in a challenging-to-manage wound. This case was successfully treated with a skin graft on a bed of collagen matrix, secured with negative pressure therapy. The choice of the appropriate technique for reconstructing skin defects depends on their depth and size. Consequently, combining these three techniques yielded a favorable functional and aesthetic outcome for the patient. This case report emphasizes the relevance of employing different techniques in managing complicated dog bites.